KONSEP POLIGAMI DALAM AL-QUR'AN: (Aplikasi Semiologi Roland Barthes) - Khikmatiar, Azkiya (QOF, 2019)
The semiology theory constructed by Roland Barthes has two stages. The first stage is called the linguistic system, while the second stage is called a mythological system. In this paper, the author tries to apply the theory to understand the concept of polygamy in the Qur'an. The result of the application of the theory in Q.S An-Nisa verse 3 is the linguistic system in the word matsna, wa tsulasa, wa ruba 'means not only the number but also means a limit of polygamy permissible. While the mythological system is allowed polygamy but it is more recommended for monogamy. The ideology contained in the verse is the ideology of feminism.